(untitled) (Global Journal of Medical Research, 2018)
The unnatural ionizing radiation emanated from Medical Diagnostic Imaging devices particular, CT and X-ray Scanners, contributes more than 50 percent of exposure to radiation globally. The technicians felt the need for deploying new technological equipment use as they consume considerably less dose for diagnosis. Hence, the management of hospitals and diagnostic centers is considering the need for swift adoption of modern and highly innovative equipments for improving patient safety and operational effectiveness. India being a country which encourages refurbished and new medical diagnostic imaging equipment, compliance with regulatory requirements for containing excessive radiation becomes critical. This research study has analyzed regulatory compliance in hospitals and diagnostic centers with 451 samples across the southern part of Tamil Nadu, India. There were seven different dependent variables namely Regulatory, Layout Engineering, Technician Competency, Human Safety, Operations Know-How, Radiation Exposure Monitoring & Top Management Commitment were studied using a structured questionnaire, and Kruskal-Wallis test was performed to compare the radiation compliance score.